New subclasses for bi-univalent functions in relation to Sălăgean integro-differential operator - Maryam S. Maje; Mustafa I. Hameed (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2026)
In this present work, two novel classes for bi-univalent functions are introduced using the recently developed Salagean integro-differential operator. Estimates for the two initial coefficients of Taylor-Maclaurin series are also provided. Furthermore, the well known Fekete-Szego functional is investigated and bounds for each of the initial coefficients for the functions belonging to this classes are obtained.